From the indigenous bands to the Congo bands of Barra do Jucu - Macedo, Inara Novaes (Revista do Colóquio, 2024)
This article presents an analysis of the congo bands of Espírito Santo, with emphasis on their origin, historical evolution and cultural importance. The object of study covers the musical practices and rituals of this manifestation, highlighting its connections with indigenous and African matrices. The research combines bibliographical review and case study, focusing on the bands of the Barra do Jucu community, considering historical, symbolic and musical aspects. The results point to a process of cultural hybridization and the analysis reveals how these bands differ from other Brazilian congados. It is concluded that the congo bands play a fundamental role in the construction of collective identities, reaffirming their value as cultural heritage of Espírito Santo and highlighting their relevance in the dialogue between memory and social transformation.